Phosphorus enrichment affects trait network topologies and the growth of submerged macrophytes. (1st January 2022) - Rao, Qingyang; Su, Haojie; Ruan, Linwei; Xia, Wulai; Deng, Xuwei; Wang, Lantian; Xu, Pengke; Shen, Hong; Chen, Jun; Xie, Ping
Abstract: Significant differences in the morphological and physiological characteristics of submerged macrophytes have been studied following nutrient addition, but little research has investigated the changes in plant trait network topology structures and trait interactions at the whole-plant perspective along nutrient gradients. Plant trait interactions and coordination strongly determine ecosystem structure and functioning. Thirty plant traits were collected from a three-month experiment to construct plant trait networks to clarify the variations in trait connections and network organization arising from five total phosphorus (TP) addition concentrations in water, including a control (CK), 0.1 (TP1), 0.2 (TP2), 0.4 (TP3), and 0.8 (TP4) mg L −1 . Nonmetric multidimensional scaling analysis showed a clear difference in the distribution of plant trait space among the different TP treatments. Distinct network structures showed that water TP-deficiency and TP-repletion changed the plant trait network into loose assemblages of more modules, which was related to low plant carbohydrate levels. Most plant functions involving biomass accumulation and carbohydrate synthesis were reduced under high TP conditions compared to moderate TP enrichment. Moreover, the percentage of significant relationships between plant functions and corresponding network modules was lower in the CK and TP4 treatments. These results suggested that low plant carbohydrates in high TP environments induced by high water chlorophyll a and tissue phosphorus could not support rapid resource transport among organs and thus inefficiently performed plant functions. Plant carbohydrates were a vital variable that impacted the network edge density, trait interactions, and plant growth. In summary, we demonstrated that high water TP enrichment reduces plant trait network connectedness and plant functional potentials, which may be correlated with reducing tissue carbohydrates. This study explores the correlations between plant trait network topology and functions to improve our understanding of physiological and ecological rules regulating trait interactions among organs and plant growth under eutrophic conditions. Highlights: Phosphorus enrichment affected plant trait network topology and trait interactions. High phosphorus changed the trait network into loose assemblages of more modules. Plant functions and plant trait network connectedness were reduced by high phosphorus. Plant carbohydrate was a key factor to impact the network structures and plant growth.